2014
DOI: 10.1111/jocn.12731
|View full text |Cite
|
Sign up to set email alerts
|

Using mobile phone text messages to improve insulin injection technique and glycaemic control in patients with diabetes mellitus: a multi‐centre study in Turkey

Abstract: Today, with the increased use of mobile communication technologies, it is possible for nurses to facilitate diabetes management by using these technologies. We believe that mobile technologies, which are not only easy to use and to follow-up with by healthcare providers, are associated with positive clinical outcomes for patients and should be more commonly used in the daily practice of diabetes management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 28 publications
0
41
0
1
Order By: Relevance
“…Research that registered unsatisfactory results adopted in its intervention a period with a mean of three months. (4)(5)(6)9,10,12,(17)(18)(19)24,26,29,31,32) This is probably due to the short interval between measurements and the delay in compliance with selfcare practices. (33) Thus, in order to obtain expressive results, it is possible to estimate as the ideal time interval for the performance of the SMS interventions of eight to 12 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research that registered unsatisfactory results adopted in its intervention a period with a mean of three months. (4)(5)(6)9,10,12,(17)(18)(19)24,26,29,31,32) This is probably due to the short interval between measurements and the delay in compliance with selfcare practices. (33) Thus, in order to obtain expressive results, it is possible to estimate as the ideal time interval for the performance of the SMS interventions of eight to 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Celik S., et al (2015) (32) "Use the insulin pen needle only once for safe and pain-free use. "; "For insulin injection, lift a skin fold with 2 or 3 fingers.…”
Section: Btmentioning
confidence: 99%
“…In some studied population was divided in two and one half was only receiving TN and the other only receiving routine care [9, 10]. In another study, all patients were receiving the TN right away, and they were they own control for evaluation of outcomes, before and after intervention [37]. The aforementioned studies have shown a more significant impact in the studied outcomes most probably because they compared the full force of the intervention against no intervention or against baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is highly recommended that the patient themselves try to manage their disease and improvement in order to be empowered against chronic diseases, which is a widely established approach. (16) Telenursing technology has been defined as a means for enhancing support in self-care and regulating the patient access to medical services, which is rapidly developing in many countries. (17) Many previous studies in this area suggested the commitment of the contactor person to presenting proper nursing care and expression of satisfaction of patients toward the high quality of these services.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%